2022
DOI: 10.1177/1934578x221142724
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacology, Phytochemistry, and Pharmacological Activities of Spatholobus suberectus Vine Stem

Abstract: Spatholobus suberectus vine stem is an important medicinal material in Chinese, Vietnamese, and Korean traditional medicines. Its decoction has long been used to treat blood disorders, such as anemia and menstrual irregularity, as well as rheumatoid diseases. Previous phytochemical investigations characterized 88 compounds from S suberectus, which mainly belonged to the phenolic class, especially of the flavonoid type. Pharmacological studies showed the beneficial effects of extracts of the plant on the cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…Therefore, the variability and potential of bajakah as a native Indonesian traditional medicine have attracted the attention of researchers in recent years. Knowledge of the variety of bajakah is very important to understand its therapeutic potential and the differences in the active substance content between the different types of bajakah [6]. A previous study reported that phenolic compounds were the dominant component of more than 50% in the 1-butanol stem fraction of 70% ethanol and water extract from bajakah (S. littoralis Hassk.)…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the variability and potential of bajakah as a native Indonesian traditional medicine have attracted the attention of researchers in recent years. Knowledge of the variety of bajakah is very important to understand its therapeutic potential and the differences in the active substance content between the different types of bajakah [6]. A previous study reported that phenolic compounds were the dominant component of more than 50% in the 1-butanol stem fraction of 70% ethanol and water extract from bajakah (S. littoralis Hassk.)…”
Section: Introductionmentioning
confidence: 99%